ENVIRONMENTAL ACTION-BASED LEARNING PROGRAMS ON CLIMATE MITIGATION: A CASE OF ECO-SCHOOLS IN KENYA - Sr. Madeleine Sophie Barat Achieng (IJRDO- Journal of Educational Research, 2024)
While there is emerging awareness of the current and potential impacts of climate change on education provision and learning, it is clear that education, both formal and non-formal, from primary through to tertiary and adult education has an important role to play in addressing climate change. Climate Change Education (CCE) at present is still a peripheral topic in both educational research and practice. In research literature, CCE has been addressed almost exclusively as a domain of science education. However, to ensure that there is effective learning and deep understanding of the subject matter, climate change education need to be integrated across school curricula at all levels. The complexities of climate change require it to be addressed using a holistic approach that draws upon a range of disciplines and areas of expertise, including climate science, policy, law, ethic, sociology, economics and culture, with the aim of an effective and inclusive knowledge sharing approach. In addition, knowledge of climate change, its science, impacts and coping measures has to be adapted to address and relate to specific target groups. Therefore, specific activities have to be developed and tailored according to age, school type and level as well as contexts and particular needs. It is against the aforementioned discourse that this paper seeks to examine the role of environmental action-based learning programs on climate mitigation in Eco-Schools in Kenya. The findings may help more schools to engage in environmental action-based learning programs to mitigate some of the effects of climate change in Kenya.